1993
DOI: 10.1111/j.1365-2958.1993.tb01735.x
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional activator HIyU of Vibrio cholerae: nucleotide sequence and role in virulence gene expression

Abstract: HlyU upregulates expression of the haemolysin, HlyA, of Vibrio cholerae. DNA sequence analysis indicates that HlyU is an 11.9 kDa protein containing a putative helix-turn-helix motif and belonging to a family of small regulatory proteins, including NoIR (Rhizobium meliloti), SmtB (Synechococcus PCC 7942) and ArsR (plasmids R773, Escherichia coli; pI258, Staphylococcus aureus; and pSX267, Staphylococcus xylosus). An hlyU mutant was constructed by insertional inactivation, and found to be deficient in the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 46 publications
0
79
0
Order By: Relevance
“…Like other hemolysins, El Tor hemolysin has been historically described as a pore-forming toxin (14,37), and its effect has been demonstrated on erythrocytes and epithelial cells (38,40). Although its role in diarrhea has been repeatedly suggested (7,21,36,40), there is only one report demonstrating cytolethal activity of El Tor hemolysin on human intestinal cells up to now (39). Here, by means of the experiments conducted in the Ussing chamber, we went on to prove that the deleterious effects introduced in the cells actually induce an inhibition of water absorption concomitant with an increase in Isc in the human small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Like other hemolysins, El Tor hemolysin has been historically described as a pore-forming toxin (14,37), and its effect has been demonstrated on erythrocytes and epithelial cells (38,40). Although its role in diarrhea has been repeatedly suggested (7,21,36,40), there is only one report demonstrating cytolethal activity of El Tor hemolysin on human intestinal cells up to now (39). Here, by means of the experiments conducted in the Ussing chamber, we went on to prove that the deleterious effects introduced in the cells actually induce an inhibition of water absorption concomitant with an increase in Isc in the human small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that expression of the HlyA haemolysin in V. cholerae is regulated by an 11.9 kDa protein designated HlyU (Williams et al, 1993). Insertional inactivation of the hlyU gene inhibited production of the HlyA haemolysin and a 28 kDa Hcp (haemolysin coregulated protein) protein.…”
Section: Discussionmentioning
confidence: 99%
“…Although by examination of their nucleotide sequence, the hlyA, hlyB and hlyC genes do not appear to comprise a classical operon, it is possible they are co-regulated at least in part by HlyU, a recently described transcriptional activator of hlyA (Williams et al, 1993). A strain containing the hlyU mutation was recently shown to be attenuated for virulence in the infant mouse model and furthermore, the observed attenuation was not fully explained by loss of HlyA expression (Williams et al, 1993). Therefore, HlyU may regulate additional virulence factors and, if it is responsible for expression of hlyC, it follows that HlyU may be a regulator that responds to in vivo environmental signals.…”
Section: In Vivo-induced Transcript Coding For a Secreted Lipasementioning
confidence: 99%